Effect of Mortar Constraint Conditions on Pullout Behavior of GFRP Soil Nails - Zhi Chen; Mengke Que; Lifei Zheng; Xiaoqinq Li; Yang Sun (Advances in Materials Science and Engineering)
Glass fiber reinforced polymer (GFRP) bars are safe, light, and environmentally friendly and, hence, have emerged as desirable alternatives to traditional steel reinforcements in soil nailing wall reinforcement. The loads experienced by GFRP soil nails are transmitted through bonding with mortar and the surrounding soil mass. Constraints of the soil mass on mortar affect the pullout performance of the nails. This paper presents a laboratory test study on the influence of different mortar constraint conditions on the pullout behavior of GFRP soil nails. The results indicated that single loading or cyclic loading has a negligible effect on the failure modes of specimens under different constraints. Therefore, all specimens underwent the same mode of failure, i.e., splitting failure of the mortar. The ultimate pullout force associated with single loading under strong constraint conditions was 77% higher than that under unconstrained conditions, and the anchorage depth increased from 0.6 m to 1.0 m. The load-slip curves obtained for unconstrained conditions and strong constraint conditions were approximately straight lines and double broken lines, respectively. The ultimate tensile stress of GFRP soil nails exceeds the tensile strength of ordinary steel bars, indicating that these nails have sufficient strength reserve.